Human capital dan masyarakat ekonomi sirkular: teologis keberlanjutan global di Indonesia - Adelia Tesalonika; Hady Sutjipto (Institute for Advanced Science Social, and Sustainable Future, 2023)
This research analyzes the relationship between human capital and its influence on circular economic development using the Environmental Quality Index (EQI) indicator in the Province of Indonesia for 2018-2021. Human capital factor analysis includes the Human Development Index (HDI), Government Expenditures, Remittances, Technology, and the Information and Communication Development Index (ICD). The method used in this research is a quantitative approach using panel data regression analysis with the Fixed Effect Model (FEM). The results of this research show that simultaneously, the human capital factor variable significantly influences the Environmental Quality Index in Indonesia. In contrast, the variables of the Human Development Index, Government Expenditure, and Technology, Information and Communication Development Index significantly influence the Environmental Quality Index. This is different from the Remittance variable, which does not significantly influence the Environmental Quality Index in Indonesia.